2013
DOI: 10.1111/j.1365-4632.2011.05340.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and cost of illness in patients with psoriasis in Malaysia: a multicenter study

Abstract: The QoL of patients with psoriasis was significantly impaired compared with that of healthy subjects and was comparable with that of patients with other chronic medical illnesses. The estimated cost of illness of psoriasis in the current study was lower than in other countries, mainly because healthcare costs in public hospitals are heavily subsidized by government and because usage of newer but more expensive treatment options is low in Malaysia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
53
2
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 23 publications
6
53
2
4
Order By: Relevance
“…While Anti-Tumor Necrosis Factor (Anti-TNF) therapy is associated with improvement in both physical and mental status in psoriasis patients, the role of this treatment on mental health is not known yet (13,14). Many studies have shown that psoriasis negatively impacts the quality of life and its co-morbid conditions (15)(16)(17)(18)(19)(20). However, our findings have not confirmed these results.…”
Section: Discussioncontrasting
confidence: 57%
“…While Anti-Tumor Necrosis Factor (Anti-TNF) therapy is associated with improvement in both physical and mental status in psoriasis patients, the role of this treatment on mental health is not known yet (13,14). Many studies have shown that psoriasis negatively impacts the quality of life and its co-morbid conditions (15)(16)(17)(18)(19)(20). However, our findings have not confirmed these results.…”
Section: Discussioncontrasting
confidence: 57%
“…347 Therefore, we performed a literature search for COI studies 348 for the period from January 2010 to December 2013 using 349 the same search terms and databases as Raho et al [9].Our 350 search identified a further nine publications [28][29][30][31][32][33][34][35][36], seven 351 of which involved psoriasis patients with biological treat-352 ment. In the COI analyses conducted by Fonia et al (UK) 353 [28] and Driessen et al (the Netherlands) [29] all patients 354 were treated with biological drugs.…”
mentioning
confidence: 99%
“…В некоторых случаях этому способствует про-водимая терапия (ПУВА, цитостатическая). В боль-шинстве исследований, проведенных в разных стра-нах [22][23][24][25]30], отмечено преобладание мужчин среди пациентов с псориазом, за исключением дан-ных, представленных малайскими и турецкими ис-следователями, отметившими небольшое преобла-дание женщин [24,26]. Чаще всего псориаз дебюти-ровал на третьем десятилетии жизни, у женщин не-сколько раньше, чем у мужчин [22,25,26].…”
Section: Discussionunclassified
“…В отличие от других на-блюдений [1,6,8], в данном исследовании было по-казано, что масса тела малайзийских пациентов не влияла на тяжесть течения псориаза. Затраты на ле-чение (исключая затраты на госпитализацию) со-ставляли в среднем 1307,47 ринггит (денежных еди-ниц Малайзии) на человека, при этом отмечалось, что пациенты тратят значительные суммы на неуч-тенные лекарственные средства, которые приобре-таются без рецепта [23]. В штате Малайзии Саравак с декабря 2007 г. по июнь 2009 г. проведены исследо-вания данных 138 пациентов с псориазом.…”
Section: ключевые слова: псориаз заболеваемость распространенностьunclassified